Experimental and Computational Insight Into Human Mesenchymal Stem Cell Paracrine Signaling and Heterocellular Coupling Effects on Cardiac Contractility and Arrhythmogenicity. Issue 4 (4th August 2017) - Mayourian, Joshua; Cashman, Timothy J.; Ceholski, Delaine K.; Johnson, Bryce V.; Sachs, David; Kaji, Deepak A.; Sahoo, Susmita; Hare, Joshua M.; Hajjar, Roger J.; Sobie, Eric A.; Costa, Kevin D.
Abstract : Rationale: : Myocardial delivery of human mesenchymal stem cells (hMSCs) is an emerging therapy for treating the failing heart. However, the relative effects of hMSC-mediated heterocellular coupling (HC) and paracrine signaling (PS) on human cardiac contractility and arrhythmogenicity remain unresolved. Objective: : The objective is to better understand hMSC PS and HC effects on human cardiac contractility and arrhythmogenicity by integrating experimental and computational approaches. Methods and Results: : Extending our previous hMSC–cardiomyocyte HC computational model, we incorporated experimentally calibrated hMSC PS effects on cardiomyocyte L-type calcium channel/sarcoendoplasmic reticulum calcium-ATPase activity and cardiac tissue fibrosis. Excitation–contraction simulations of hMSC PS-only and combined HC+PS effects on human cardiomyocytes were representative of human engineered cardiac tissue (hECT) contractile function measurements under matched experimental treatments. Model simulations and hECTs both demonstrated that hMSC-mediated effects were most pronounced under PS-only conditions, where developed force increased ≈4-fold compared with non–hMSC-supplemented controls during physiological 1-Hz pacing. Simulations predicted contractility of isolated healthy and ischemic adult human cardiomyocytes would be minimally sensitive to hMSC HC, driven primarily by PS. Dominance of hMSC PS was also revealed in simulations of fibrotic cardiac tissue, where hMSC PS protected from potential proarrhythmic effects of HC at various levels of engraftment. Finally, to study the nature of the hMSC paracrine effects on contractility, proteomic analysis of hECT/hMSC conditioned media predicted activation of PI3K/Akt signaling, a recognized target of both soluble and exosomal fractions of the hMSC secretome. Treating hECTs with exosome-enriched, but not exosome-depleted, fractions of the hMSC secretome recapitulated the effects observed with hMSC conditioned media on hECT-developed force and expression of calcium-handling genes (eg, SERCA2a, L-type calcium channel). Conclusions: : Collectively, this integrated experimental and computational study helps unravel relative hMSC PS and HC effects on human cardiac contractility and arrhythmogenicity, and provides novel insight into the role of exosomes in hMSC paracrine-mediated effects on contractility. Abstract : Supplemental Digital Content is available in the text.